Center-Pivot-Irrigated Corn Silage Cost-Return Budget (Custom Harvested) - O'Brien, Daniel M.; Dumler, Troy J. (My University, 1999)
This publication projects a budget that reflects expected income and costs based on center-pivot-irrigated corn silage production in Kansas.
MF589_1999_10
Keywords: MF589; Economics; Crops; MF